COMPARATIVE ANALYSIS OF MEDICAL EQUIPMENT USED IN DIAGNOSTIC IMAGING IN BULGARIA AND COUNTRIES WORLDWIDE AND OPTIMIZATION AIMED AT IMPROVING THE HEALTH CARE SYSTEM MANAGEMENT - Svetoslav Garov; Tsvetelina Mihaylova; Galina Makedonska (Peytchinski Publishing, 2016)
Purpose: to reveal the current condition of medical equipment in Bulgaria related to those major groups of socially significant diseases and to make an attempt to define guidelines for its optimization in view of improving the functioning and management of the healthcare system in this field. Material and methods: The following research methods have been applied: 1. Document review method - research, processing and analysis of medical statistical information taken from data from WHO and annual reports of NRA. The study includes data from 2009 - 2015. 2. Graphical method - summarizing data in relevant tables and diagram presentations. Results: The article analyzes the condition of medical equipment in the field of oncologic and cardiologic medical aid in Bulgaria based on data taken from WHO (World Health Organization) and annual reports of NRA (Nuclear Regulatory Agency). Six types of diagnostic imaging and radiation therapy devices have been studied: Magnetic Resonance Imaging units (MRI); Computed Tomography Scanners (CT), Positron Emission Tomography Scanners, Mammographs, Linear accelerators and Telecobalt units (Cobalt-60). The condition of medical equipment since 2009 has been analyzed, results have been reported and trends - studied. Conclusion: The oncologic and cardiologic medical equipment in Bulgaria has been gradually improving in the last seven years, but quantitative indicators regarding the devices studied are still far away from the figures recommended by WHO with one single exception, i.e. Computed Tomography Scanners.